Manufacturing method of rare earth magnet joint and rare earth magnet joint
Patent Information
- Application Number
- JP2024105271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2041-02-09
AI Technical Summary
Existing methods for joining multiple Nd-Fe-B sintered magnets in electric motors face challenges such as high cost, inefficiency, and reduced workability due to the need for additional processes like adhesive bonding, which lack high dimensional accuracy and require significant space and energy consumption.
A method involving the use of an inkjet technique to apply a continuous ultraviolet curable resin coating across the edges of adjacent Nd-Fe-B sintered magnets, forming a film with specific thickness and density to bond the magnets, providing insulation and corrosion resistance.
This method enables low-cost, high-dimensional accuracy bonding of Nd-Fe-B sintered magnets with improved insulation and corrosion resistance, reducing the need for additional processing steps and energy consumption.
Smart Images

Figure 00000000_0000_ABST 
Figure 00000000_0001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a rare earth magnet joined body in which a plurality of rare earth magnets such as Nd-Fe-B sintered magnets are joined together, and to a rare earth magnet joined body formed by joining a plurality of rare earth magnets together. [Background technology]
[0002] Nd-Fe-B sintered magnets are obtained by compressing and sintering alloy powder, and applications include electric motors for automobiles. If the laminated steel plates and magnets in the rotor core of an electric motor are not insulated from each other, eddy currents generated in the magnets can flow through the laminated steel plates to other magnets inserted in adjacent slots, resulting in relatively large loops of eddy currents. As a result, the eddy currents cause the magnets to rise in temperature, resulting in heat loss and a deterioration in magnetic properties, making it difficult to achieve the desired performance in the electric motor.
[0003] One of the countermeasures to these problems in electric motors is to form a coating on the surface of a Nd-Fe-B sintered magnet to improve its insulation and corrosion resistance, thereby suppressing eddy currents (for example, JP 2011-193621 A (Patent Document 1)).
[0004] Representative surface treatment methods for imparting insulation to sintered Nd-Fe-B magnets include resin spray painting and electrodeposition painting. However, in the case of spray painting, a certain percentage of the paint is lost because it is sprayed. In addition, in the case of thermosetting resins that are generally used in spray painting and electrodeposition painting, heating with a heater is essential for drying and baking after painting, and the heat treatment furnaces generally used in this process consume a lot of time and energy to harden the resin. Furthermore, since a large space is required to install the equipment, the cost of surface treatment of magnets tends to be high with conventional methods.
[0005] One way to reduce the cost of the above-mentioned surface treatment is to form a coating using ultraviolet-curing resin. Because ultraviolet-curing resin is cured by ultraviolet light, it is possible to form a coating in a short time, at low cost, and in a small space compared to heat curing in a heat treatment furnace. One method of applying ultraviolet-curing resin is to immerse the magnet body in the resin, rotate it to remove excess uncured components, and then cure it by irradiating it with ultraviolet light. However, a more uniform method of applying the resin is to apply it using an inkjet method, which can form a uniform film in a short time, at low cost, and in a simple manner. As a result, it has become possible to easily impart insulation to magnets.
[0006] Another solution to the problems with electric motors mentioned above is to divide the magnet. That is, by dividing the Nd-Fe-B sintered magnet in the slot into multiple pieces, it is possible to physically impede the transmission of electrons and suppress eddy currents. However, dividing the magnet increases the number of magnets that need to be handled, which creates a problem of reduced workability in the assembly process, such as inserting them into the slots. To address this problem, methods have been devised such as joining multiple magnets with an adhesive or fixing them with insulating tape (for example, JP 2015-61328 A (Patent Document 2)). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2011-193621 A [Patent Document 2] JP 2015-61328 A Summary of the Invention [Problem to be solved by the invention]
[0008] The above-mentioned method of joining multiple divided magnets with adhesive and the method of fixing divided magnets described in Patent Document 2 both have drawbacks, such as not being able to achieve high dimensional accuracy and requiring increased work.
[0009] The present invention has been made in view of the above circumstances, and has an object to provide a method for manufacturing a rare earth magnet joined body formed by joining a plurality of rare earth magnets, which can join a plurality of rare earth magnets in a simple manner and at the same time impart corrosion resistance and insulation properties, and a rare earth magnet joined body manufactured by such a method. [Means for solving the problem]
[0010] As a result of intensive research by the inventors in order to achieve the above-mentioned object, they have discovered that, when joining a plurality of rare earth magnets to produce a rare earth magnet joined body, it is possible to join a plurality of rare earth magnets to form a rare earth magnet joined body by bringing one surface of the rare earth magnets to be joined into contact with each other, forming a continuous coating across the edges of the contact surface and over both adjacent surfaces of the rare earth magnets, thereby joining the two rare earth magnets, using a relatively low-cost and simple method of coating formation, and that the coating formed at the same time can impart corrosion resistance and insulation to the rare earth magnets, thereby completing the present invention.
[0011] Therefore, the present invention provides the following method for producing a rare earth magnet assembly, and the following rare earth magnet assembly obtained by the manufacturing method. 1. A method for manufacturing a rare earth magnet joint by joining a plurality of rare earth magnets, comprising: bringing one surface of the rare earth magnets to be joined into contact with each other; ejecting droplets of a resin composition from the tip of a head by an inkjet method in which droplets are ejected from a head onto at least a portion of the adjacent surfaces of the rare earth magnets adjacent to each other across the edge of the contact surfaces; and hardening the attached resin composition to form a continuous film having an average thickness of 30 to 90 μm and a film density of 1.15 to 1.21 g / cm that is continuous across the edge of the contact surfaces and across the adjacent surfaces. 3 and bonding adjacent rare earth magnets to each other. 2. The method for producing a rare earth magnet joint as described in 1, wherein one or both of the rare earth magnets to be joined together is already a joint formed by joining a plurality of rare earth magnets together. 3. The method for producing a rare earth magnet joint according to 1 or 2, wherein the operation of depositing droplets of the resin composition on both adjacent surfaces and curing the deposited resin composition are repeated multiple times to form the coating. 4. The method for producing a rare earth magnet joint according to any one of 1 to 3, wherein the resin composition is an ultraviolet curable resin composition, and the resin composition attached to both adjacent surfaces is irradiated with ultraviolet light to cure the resin composition. 5. The method for producing a rare earth magnet assembly according to any one of 1 to 4, wherein the rare earth magnet assembly has a rectangular parallelepiped shape and the coating is formed on at least two of a plurality of faces including the edge of the contact surface. 6. A method for producing a rare earth magnet joint as set forth in any one of 1 to 5, comprising applying a primer to the adjacent surface of the rare earth magnet on which the coating is to be formed and / or to at least a portion of the coating already formed on the adjacent surface, and then forming the coating. 7. In a rare earth magnet joint formed by joining a plurality of rare earth magnets, for at least one pair of rare earth magnets constituting the rare earth magnet joint, a cured coating of a resin composition is applied by an inkjet method to at least a part of adjacent surfaces of the two rare earth magnets adjacent to each other across an edge of a joining surface where one surface of the rare earth magnets are in contact with each other and joined, and the coating has an average thickness of 30 to 90 μm and a film density of 1.15 to 1.21 g / cm. 3 wherein rare earth magnets are joined together by the coating. 8. A rare earth magnet joint as set forth in claim 7, wherein the hardness of said coating is 6H or more in terms of pencil hardness as specified in JIS K 5600. Effect of the Invention
[0012] According to the present invention, a rare earth magnet joint body can be produced by joining a plurality of rare earth magnets with good dimensional accuracy by a low-cost and simple method, and at the same time, it is also possible to impart corrosion resistance and insulation properties to the rare earth magnets. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic perspective view illustrating an example of a method for producing a rare earth magnet assembly of the present invention, and showing an example of a rare earth magnet assembly of the present invention obtained by the method. [Diagram 2] 2 is a scanning electron microscope (SEM) photograph showing a coating at a joint portion of the rare earth magnet joint obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will now be described in further detail. In the manufacturing method of the rare earth magnet joined body of the present invention, as described above, a rare earth magnet joined body is produced in which a plurality of rare earth magnets are joined together by forming a coating that covers both rare earth sintered magnets to be joined together.
[0015] Specifically, for example, when joining rectangular parallelepiped rare earth magnets 1a and 1b as shown in Fig. 1, first, as shown in Fig. 1(A), one surface 3a, 3b of the rare earth magnets 1a and 1b to be joined are brought into contact with each other. This contact surface 3ab becomes the joining surface of the joined body 1 obtained. Next, as shown in Fig. 1(B), continuous coatings 2, 2 are formed across the edges of the contact surface 3ab (joining surface) on at least a part of the adjacent surfaces 4a, 4b of the two rare earth magnets 1a and 1b adjacent to each other across the edge of the contact surface 3ab (joining surface) (most of the two surfaces in Fig. 1(B)), and the two rare earth magnets 1a and 1b are joined by the coatings 2, 2 to obtain the rare earth magnet joined body 11 of the present invention.
[0016] Here, in terms of the surface on which the coating 2 is formed, for example, when the obtained rare earth magnet joint 11 has a rectangular parallelepiped shape, it is preferable from the viewpoint of joint strength to form the coating 2 on two or more surfaces including the edge of the contact surface (joining surface) 3ab as shown in Fig. 1. Also, the area of the coating 2 is not particularly limited, but it is preferable that it is as large as possible from the viewpoints of joint strength, corrosion resistance, and insulating property.
[0017] 1, a pair of identically shaped rare earth magnets 1a, 1b are joined to form the rare earth magnet joined body 11, but the rare earth magnets may be different in shape or size, and three or more rare earth magnets may be joined to form a rare earth magnet joined body. Furthermore, one or both of the rare earth magnets to be joined together may already be a joined body in which multiple rare earth magnets are joined, and in that case, the magnet in which multiple rare earth magnets are already joined may be joined by forming a coating as in the present invention, or may be joined by some other method.
[0018] The rare earth magnets to be subjected to the joining operation are not particularly limited, but for example, sintered magnets such as Nd-Fe-B sintered magnets and SmCo sintered magnets are preferably used as the objects of joining. Since multiple rare earth magnets are fixed together by forming a coating, which will be described later, it is preferable that the shape of the rare earth magnets is such that the coating surface of the rare earth magnets and the joining surface between the rare earth magnets are flat, and specifically, a rectangular parallelepiped shape is most suitable.
[0019] The means for forming the coating is not particularly limited, and can be, for example, a known method such as spray coating, etc. In order to obtain a more preferable effect, for example, an inkjet method in which droplets of a resin composition are ejected from a head can be applied, and more preferably, an ultraviolet-curable resin composition can be applied as the resin composition.
[0020] Hereinafter, as one embodiment of the film-forming operation in the production method of the present invention, a case where a film is formed by an ink-jet method using an ultraviolet-curable resin composition will be described. The method of forming a coating by an inkjet system includes: (A) a step of ejecting droplets of an ultraviolet-curable resin composition from the tip of a head using an inkjet system that ejects droplets from a head, thereby adhering the composition to the surface of a rare earth magnet; and (B) a step of irradiating the ultraviolet-curable resin composition adhered to the surface of the rare earth magnet with ultraviolet light, thereby curing the ultraviolet-curable resin.
[0021] In the above steps (A) and (B), the ultraviolet curing resin is applied and cured as a continuous coating 2 across the edges of the contact surface (joint surface) 3ab of the rare earth magnets 1a, 1b to be joined, as described with reference to Fig. 1, and the multiple magnets are joined by the mechanical strength of the ultraviolet curing resin and the bonding strength to the rare earth magnet surfaces. In this case, when three or more rare earth magnets are joined, the coating may be continuous across the adjacent surfaces of the three or more magnets.
[0022] The thickness (average film thickness) of such a coating is not particularly limited, but is usually 30 μm or more, preferably 40 μm or more, and more preferably 50 μm or more. Also, it is usually 90 μm or less, preferably 80 μm or less, and more preferably 70 μm or less. If the thickness of the coating is within the above range, the corrosion resistance and insulation properties are good, and it is possible to obtain a rare earth magnet assembly having sufficient electrical resistance as a magnet for motor applications, for example.
[0023] In the above step (A), droplets of the ultraviolet curable resin composition are ejected from the tip of the head by an inkjet method that ejects droplets from a head, and the ultraviolet curable resin composition is adhered to the surface of the rare earth magnet. Devices that apply the inkjet method are generally known as inkjet printers, which eject fine droplets of a liquid coating material and adhere them directly to the surface of an object. In addition to devices that print ink on paper, devices that eject uncured resin compositions instead of ink and adhere them directly to the surface of an object are also commercially available, and in this case, they are also usually called inkjet printers. There are two types of inkjet methods: a continuous type that constantly ejects a liquid coating material, and an on-demand type that ejects a liquid coating material only when necessary. There are two further types of on-demand types: a piezoelectric type that ejects a liquid coating material using a piezoelectric element, and a thermal type that ejects a liquid coating material using bubbles generated by heating. In the present invention, although there is no particular limitation, an on-demand type is preferred because it is relatively easy to reduce the size of the device, and a piezoelectric type is preferred because the ultraviolet-curable resin composition may be cured by heat.
[0024] By applying the ultraviolet curing resin to form the coating and the inkjet method to inject the ultraviolet curing resin composition, a uniform coating can be formed. This makes it possible to obtain uniform bonding strength and further suppress the dimensional error of the rare earth magnet assembly. In addition, by repeating steps (A) and (B), the film thickness can be increased and the bonding strength can be improved.
[0025] The resolution when applying the ultraviolet curable resin composition by the inkjet method is preferably 300 dpi or more, particularly 600 dpi or more, and particularly 1000 dpi or more. By increasing the resolution and making the droplets finer, the unevenness of the formed coating and uncovered parts such as pinholes are reduced, and the density of the coating is increased, so that the bonding strength is increased. On the other hand, taking into consideration the effect of the internal stress of the coating caused by increasing the resolution and increasing the density of the coating, the resolution is usually preferably 1200 dpi or less. Note that only one droplet may be applied to one dot, or two or more droplets may be applied to one dot.
[0026] When using the inkjet method, the amount of liquid in the droplets is selected according to the thickness and resolution of the coating. Considering the characteristics of the coating to be formed and the production efficiency, the amount is preferably 3 pL or more, particularly 6 pL or more, and 20 pL or less, particularly 12 pL or less, and especially 10 pL or less per droplet. In addition, the viscosity of the ultraviolet curing resin composition forming the droplets is preferably 17 mPa / s or more and 27 mPa / s or less at 25°C. Here, although not particularly limited, a primer layer may be formed on a part or all of the coating surface of the rare earth magnet before the ultraviolet curing resin composition is attached, in order to improve the adhesion of the coating. In this case, if one or both of the rare earth magnets to be joined are a joint in which a plurality of magnets have already been joined by the joining method of the present invention by forming a coating, a primer layer can also be formed on the coating.
[0027] In the case of forming a coating by the inkjet method of the present invention, it is possible to increase the coating density by controlling the resolution and the amount of liquid droplets described above. The coating density is preferably 1.15 g / cm 3 More preferably, 1.17 g / cm 3 or more, preferably 1.21 g / cm 3 Less than or equal to 1.19 g / cm 3 The coating density in this range can satisfactorily suppress problems such as peeling and cracking of the coating while ensuring high bonding strength. Furthermore, the coating density in this range can provide good corrosion resistance and insulation. The coating density can be calculated from the film thickness and the coating mass when the coating is formed on a specified area.
[0028] In one embodiment of the present invention, when manufacturing a rare earth magnet joint, there is an advantage that dimensional adjustment such as surface polishing is not required because there is no adhesive overflow, compared to joining with a normal adhesive. In addition, there is no process of applying adhesive, fixing the magnet, and hardening by drying or heating, and it is possible to manufacture a rare earth magnet joint with one coating.
[0029] In this embodiment, the ultraviolet curing resin used as the resin for forming the coating is a resin that undergoes a photochemical reaction by the energy of ultraviolet light and hardens from a liquid to a solid in seconds. The ultraviolet curing resin composition (uncured ultraviolet curing resin) contains a photopolymerizable compound (monomer or resin precursor) as the main component, a photopolymerization initiator, a colorant, an auxiliary, and the like. Examples of the photopolymerizable compound include radical-type acrylic monomers that undergo polymerization by cleavage of double bonds. Other examples include, but are not limited to, cationic epoxy monomers, oxetane monomers, vinyl ether monomers, and the like. In the radical type, the photopolymerization initiator is decomposed by light to generate radicals, which react with the monomer to generate new radicals, thereby progressing the polymerization. Examples of the photopolymerization initiator species in this case include aromatic ketones. On the other hand, in the cationic type, the photopolymerization initiator is decomposed by light to generate acids, which react with the monomer to generate new cationic active species, thereby progressing the polymerization. Examples of the photopolymerization initiator species in this case include triallylsulfonium cations and hexafluorophosphate. An example of a coloring agent is carbon black, which also contributes to improving the visibility of the rare earth magnet after the coating is formed.
[0030] In the above step (B), the ultraviolet curable resin composition attached to the surface of the rare earth magnet in step (A) is irradiated with ultraviolet light to cure the ultraviolet curable resin composition. The ultraviolet light is appropriately selected depending on the type of ultraviolet curable resin composition used, but ultraviolet light with a wavelength of about 200 to 380 nm can usually be used. The ultraviolet light can be irradiated from, for example, a mercury lamp, a UV-LED, a xenon lamp, etc.
[0031] In the coating formation method using the inkjet system, which is one embodiment of coating formation in the production method of the present invention, the above steps (A) and (B) can be carried out, for example, as in the following embodiment (1) or (2).
[0032] Mode (1): In step (A), while moving the tip of the head near the rare earth magnet, droplets of the ultraviolet curable resin composition are sequentially ejected onto the coating surface of the magnet, and the droplets are linked together, so that the linked droplets of the ultraviolet curable resin composition adhere to some or all of the adjacent surfaces of the rare earth magnets (for example, adjacent surfaces 4a, 4b in FIG. 1), and a continuous thin layer of the ultraviolet curable resin composition is formed across the contact surface (joint surface) between the rare earth magnets (for example, contact surface (joint surface) 3ab in FIG. 1). Next, the above step (B) is carried out to harden the thin layer of the ultraviolet curable resin composition to form a coating, and the multiple rare earth magnets are connected and fixed by this coating. At this time, in order to increase the film thickness, steps (A) and (B) can be carried out multiple times to stack thin films of the ultraviolet curable resin composition to form a multi-layered coating.
[0033] Mode (2): In step (A), droplets of the ultraviolet curable resin composition are ejected from the tip of the head, and step (B) is performed on the droplets successively or at any time. The tip of the head is moved to an adjacent portion of the ultraviolet curable resin where the droplets have hardened, and steps (A) and (B) are further performed repeatedly, and this is performed on the planned range of film formation while moving the tip of the head near the surface of the rare earth magnet. In this way, a continuous film made of the ultraviolet curable resin composition is formed on part or all of the adjacent surfaces of the multiple rare earth magnets (e.g., adjacent surfaces 4a, 4b in FIG. 1) across the contact surfaces (joint surfaces) between the rare earth magnets (e.g., contact surface (joint surface) 3ab in FIG. 1).
[0034] The time (timing) from when the droplets are applied to the surface of the rare earth magnet until the start of UV irradiation (the start of curing) is not particularly limited. However, from the viewpoint of preventing inconveniences such as variations in the thickness of the coating formed due to aggregation of the droplets, the above-mentioned mode (2) in which the coating is cured substantially simultaneously with the application of the droplets (for example, from immediately after the droplets are ejected to immediately after the droplets are applied) is preferably adopted.
[0035] In the case of irradiating ultraviolet rays substantially at the same time as the droplets are attached to the surface of the rare earth magnet as in the above-mentioned mode (2), it is effective to provide an ultraviolet ray irradiating section at or near the tip of the head that ejects the droplets of the ultraviolet curing resin composition, either as part of the head or as a separate section from the head. For example, if an ultraviolet curing inkjet printer or the like is used that has an ultraviolet ray irradiating section at or near the tip of the head that ejects the droplets of the ultraviolet curing resin composition, either as part of the head or as a separate section from the head, the ultraviolet curing resin composition can be cured at the spot where the droplets are ejected from the head, which is more advantageous since it is not necessary to perform a drying process or a heat treatment process in a separate device, as is performed in the formation of a coating by spray painting. In addition, in this case, if the timing of ultraviolet irradiation is controlled, it is also possible to irradiate ultraviolet rays after holding the droplets for a certain period of time after the droplets are attached, and ultraviolet rays can be irradiated without moving the head or after moving the tip of the head to a portion adjacent to the ultraviolet curing resin composition to which the droplets are attached.
[0036] On the other hand, when droplets are attached to the surface of the rare earth magnet, and then the droplets are held for a certain period of time before being irradiated with ultraviolet light, particularly in the case of the above-mentioned embodiment (1), an ultraviolet light irradiation device such as an ultraviolet lamp may be provided separately from the inkjet printer, and the droplets of the ultraviolet curable resin composition or a thin layer of the ultraviolet curable resin composition formed by linking the droplets of the ultraviolet curable resin composition may be held for a certain period of time as necessary before being irradiated with ultraviolet light all at once to carry out step (B).
[0037] When carrying out steps (A) and (B), from the viewpoint of obtaining good bonding and dimensional accuracy, it is preferable to form the coating in a single flow without moving the rare earth magnet or removing it from the device. For example, if an inkjet printer is used, steps (A) and (B) can be carried out in a single operation, so that the rare earth magnet is less likely to shift, and furthermore, if a jig or the like is used, dimensional errors can be suppressed.
[0038] The coating surfaces of the rare earth magnets are usually arranged in a direction perpendicular to the ejection direction of the droplets. For example, when the rare earth magnet is a rectangular parallelepiped, when one side is coated, only one side is connected and fixed by the coating, and the bonding surface is not completely fixed, so it is difficult to treat the rare earth magnets as one bonded body. Therefore, it is preferable to form a coating on at least two or more surfaces when the rare earth magnet bonded body is formed, such as the coating 2, 2 of the rare earth magnet bonded body 11 illustrated in FIG. 1(B) above. In order to form a coating on two surfaces of the rare earth magnet bonded body, for example, after coating one surface, it is necessary to rotate the rare earth magnet bonded body and coat it. At this time, if a gap occurs between the coated surfaces of the rare earth magnets to be bonded due to warping of the coating, the bonding will not go well, so it is preferable that the interval between the coated surfaces is narrow.
[0039] In the present invention, in the method for forming a coating by the inkjet method, when the droplets of the ultraviolet curable resin composition are ejected from the tip of the head in the step (A) and when the ultraviolet rays are irradiated in the step (B), the surface of the rare earth magnet can be arranged so as to be inclined from the direction perpendicular to the droplet ejection direction. When the rare earth magnet has a rectangular parallelepiped shape, the surface of the rare earth magnet can be inclined, for example, by 45°, so that two adjacent faces can be processed simultaneously. When the surface of the rare earth magnet is arranged so as to be inclined from the direction perpendicular to the droplet ejection direction, it is preferable to apply mode (2).
[0040] The coating formed in the present invention is not particularly limited, but preferably has a pencil hardness of 6H or more according to JIS K 5600. With such a hardness, the coating is less likely to peel off, and good bonding strength can be obtained.
[0041] The joining strength between the rare earth magnets in the rare earth magnet joint obtained by the manufacturing method of the present invention can be evaluated by measuring the transverse rupture strength, for example, by carrying out a three-point bending test at 250 kN with an AG-I manufactured by Shimadzu Corporation. Although not particularly limited, it is preferable that the average transverse rupture strength is 60 N or more. EXAMPLES
[0042] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.
[0043] [Example 1] A rectangular parallelepiped (14.23 mm x 7.06 mm x 5.16 mm) Nd-Fe-B sintered magnet was prepared and fixed in a jig as a pair, and then a continuous coating (2) was formed across the edge of the contact surface (joint surface) (3ab) of both magnets (1a, 1b) on both adjacent surfaces (4a, 4b) adjacent to each other across the edge of the contact surface (joint surface) (3ab) using a UV-LED curing flat head inkjet printer UFJ-6042MkII (Made by Mimaki Engineering Co., Ltd.) as in the example shown in Figure 1 (B). The ultraviolet curing resin composition used to form the coating was mainly composed of acrylic ester, and contained hexamethylene diacrylate as a reactive diluent, a polymerization initiator, and carbon black as a colorant. The amount of droplets of the ultraviolet curable resin composition discharged by the inkjet printer was 10 pL, and the resolution was 1200 dpi x 1200 dpi. The film formation operation was carried out as follows.
[0044] The head tip was moved near the surface of the rare earth magnet to sequentially eject droplets of the ultraviolet-curable resin composition onto the entire surface (total of 14.23 mm x 14.12 mm) consisting of the two adjacent surfaces (4a, 4b) of the two combined Nd-Fe-B sintered magnets, forming a thin layer of the ultraviolet-curable resin composition, and then immediately irradiated with ultraviolet light to form a coating of the ultraviolet-curable resin. The rare earth magnet was then turned 180 degrees, and a coating was formed in the same manner as before, forming coatings on the two opposing surfaces to join the Nd-Fe-B sintered magnets. This operation was performed on three sets of Nd-Fe-B sintered magnets, and three rare earth magnet joints were obtained.
[0045] The resulting Nd-Fe-B sintered magnet joint was subjected to a three-point bending test at 250 kN using Shimadzu Corporation's AG-I to measure the transverse rupture strength and evaluate the joint strength. The average transverse rupture strength was 114.5 N, which is sufficient for use in an electric motor. The hardness of the coating was measured using a pencil hardness tester conforming to JIS K 5600 and found to be 6H or higher. Furthermore, when the cross section of the joint was observed with a scanning electron microscope (SEM), as shown in Figure 2, part of the ultraviolet curing resin forming the coating had penetrated into the gaps in the joint surface. Note that the dark gray area appearing above the coating in Figure 2 is the background and is not part of the joint.
[0046] In addition, the dimensions of 30 rare earth magnet joints produced in the same manner were measured with a Mitutoyo Corporation digital caliper, and a comparison was made before and after joining, revealing that the dimensional variation was within ±0.8%. The height relative to the surface on which the coating is formed includes the film thickness and surface roughness of the film, resulting in a variation of ±0.8%, but the dimensions of the non-coated parts showed even smaller variation, falling within ±0.5%. In this way, rare earth magnet joints with good dimensional accuracy were obtained.
[0047] Next, to check the heat resistance of the coating, it was heated in an oven at 160 degrees. After 24 hours, it was removed from the oven and the surface was observed, but no significant changes were observed. In addition, when a similar rare earth magnet joint was sandwiched between electrodes and pressurized to 7 MPa, the electrical resistance was measured using a connected resistance meter, which was 1 MΩ or more, indicating good electrical resistance.
[0048] Furthermore, in order to investigate the condition of the coating, a 10 mm x 10 mm ultraviolet curing resin coating was formed on a 29 mm x 18 mm x 2 mm Nd-Fe-B sintered magnet under the same conditions as in Example 1. The average thickness of the entire ultraviolet curing resin coating formed was measured with a Mitutoyo Corporation digital indicator and found to be 81.6 μm. The coating density calculated from the area of the surface on which the coating was formed, the coating thickness, and the change in weight of the rare earth magnet before and after coating formation was 1.18 g / cm. 3 It was.
[0049] [Example 2] Three rare earth magnet assemblies were obtained in the same manner as in Example 1, except that the amount of the droplets of the ultraviolet curable resin composition was 6 pL and the resolution was 600 dpi×600 dpi.
[0050] The resulting Nd-Fe-B sintered magnet joint was subjected to a three-point bending test at 250 kN using an AG-I made by Shimadzu Corporation to measure the transverse rupture strength and evaluate the joint strength. The average transverse rupture strength was 66.3 N, which was sufficient for use in an electric motor. As in Example 1, the hardness of the coating was measured with a pencil hardness tester and found to be 6H or more. Furthermore, when the cross section of the joint was observed with an SEM, it was found that part of the ultraviolet curing resin had penetrated into the gaps in the joint surface.
[0051] In addition, the dimensions of 30 rare earth magnet joints produced in the same manner were measured with a Mitutoyo Corporation digital caliper, and a comparison was made before and after joining, revealing that the dimensional variation was within ±0.8%. The height relative to the surface on which the coating is formed includes the film thickness and surface roughness of the film, resulting in a variation of ±0.8%, but the dimensions of the non-coated parts showed even smaller variation, falling within ±0.5%. In this way, rare earth magnet joints with good dimensional accuracy were obtained.
[0052] Next, to check the heat resistance of the coating, it was heated in an oven at 160 degrees. After 24 hours, it was removed from the oven and the surface was observed, but no significant changes were observed. In addition, when a similar rare earth magnet joint was sandwiched between electrodes and pressurized to 7 MPa, the electrical resistance was measured using a connected resistance meter, which was 1 MΩ or more, indicating good electrical resistance.
[0053] Furthermore, in order to investigate the condition of the coating, a 10 mm x 10 mm ultraviolet curing resin coating was formed on a 29 mm x 18 mm x 2 mm Nd-Fe-B sintered magnet under the same conditions as in Example 2. The average thickness of the entire ultraviolet curing resin coating formed was measured with a Mitutoyo Corporation digital indicator and found to be 42.3 μm. The coating density calculated from the area of the surface on which the coating was formed, the coating thickness, and the change in weight of the rare earth magnet before and after coating formation was 1.17 g / cm. 3 It was.
[0054] [Example 3] Three rare earth magnet joints were obtained in the same manner as in Example 1, except that the amount of the droplets of the ultraviolet curable resin composition was 8 pL.
[0055] The resulting Nd-Fe-B sintered magnet joint was subjected to a three-point bending test at 250 kN using an AG-I made by Shimadzu Corporation to measure the transverse rupture strength and evaluate the joint strength. The average transverse rupture strength was 64.1 N, which was sufficient for use in an electric motor. As in Example 1, the hardness of the coating was measured with a pencil hardness tester and found to be 6H or more. Furthermore, when the cross section of the joint was observed with an SEM, it was found that part of the ultraviolet curing resin had penetrated into the gaps in the joint surface.
[0056] In addition, the dimensions of 30 rare earth magnet joints produced in the same manner were measured with a Mitutoyo Corporation digital caliper, and a comparison was made before and after joining, revealing that the dimensional variation was within ±0.8%. The height relative to the surface on which the coating is formed includes the film thickness and surface roughness of the film, resulting in a variation of ±0.8%, but the dimensions of the non-coated parts showed even smaller variation, falling within ±0.5%. In this way, rare earth magnet joints with good dimensional accuracy were obtained.
[0057] Next, to check the heat resistance of the coating, it was heated in an oven at 160 degrees. After 24 hours, it was removed from the oven and the surface was observed, but no significant changes were observed. In addition, when a similar rare earth magnet joint was sandwiched between electrodes and pressurized to 7 MPa, the electrical resistance was measured using a connected resistance meter, which was 1 MΩ or more, indicating good electrical resistance.
[0058] Furthermore, in order to investigate the condition of the coating, a 10 mm x 10 mm ultraviolet curing resin coating was formed on a 29 mm x 18 mm x 2 mm Nd-Fe-B sintered magnet under the same conditions as in Example 3. The average thickness of the entire ultraviolet curing resin coating formed was measured with a Mitutoyo Corporation digital indicator and found to be 65.8 μm. The coating density calculated from the area of the surface on which the coating was formed, the coating thickness, and the change in weight of the rare earth magnet before and after coating formation was 1.18 g / cm. 3 It was. [Explanation of symbols]
[0059] 1a,1b Rare earth magnet 11 Rare earth magnet assembly 2 Coating 3a, 3b One side of rare earth magnet 3ab Contact surface (joint surface) 4a,4b adjacent surfaces
Claims
1. A method for manufacturing a rare earth magnet joint by joining a plurality of rare earth magnets, comprising: bringing one surface of the rare earth magnets to be joined into contact with each other; ejecting droplets of a resin composition from the tip of a head using an inkjet method in which droplets are ejected from a head onto at least a portion of the adjacent surfaces of both rare earth magnets adjacent to each other across the edges of the contact surfaces; and hardening the attached resin composition to form a coating having an average thickness of 30 to 90 μm that is continuous across both adjacent surfaces across the edges of the contact surfaces, thereby joining the adjacent rare earth magnets to each other.
2. A method for manufacturing a rare earth magnet joint by joining a plurality of rare earth magnets, comprising the steps of: bringing one surface of the rare earth magnets to be joined into contact with each other; using an inkjet method in which droplets are ejected from a head onto at least a portion of the adjacent surfaces of both adjacent rare earth magnets across the edges of the contact surfaces, ejecting droplets of a resin composition from the tip of a head to adhere to both adjacent surfaces of the rare earth magnets to be joined; hardening the adhered resin composition to form a coating having a film density of 1.15 to 1.21 g / cm 3 that extends across the edges of the contact surfaces and continues across both adjacent surfaces, thereby joining adjacent rare earth magnets together.
3. The method for producing a rare earth magnet joint according to claim 1, wherein the film density of said coating is 1.15 to 1.21 g / cm 3 .
4. 4. The method for producing a rare earth magnet joint according to claim 1, wherein one or both of the rare earth magnets to be joined together is already a joint formed by joining a plurality of rare earth magnets together.
5. The method for producing a rare earth magnet joint according to any one of claims 1 to 4, wherein an operation of depositing droplets of the resin composition on both adjacent surfaces and an operation of curing the deposited resin composition are repeated multiple times to form the coating.
6. The method for producing a rare earth magnet joint according to any one of claims 1 to 5, wherein the resin composition is an ultraviolet curable resin composition, and the resin composition attached to both adjacent surfaces is irradiated with ultraviolet light to cure the resin composition.
7. The method for manufacturing a rare earth magnet assembly according to any one of claims 1 to 6, wherein the rare earth magnet assembly has a rectangular parallelepiped shape, and the coating is formed on two or more of a plurality of surfaces including an edge portion of the contact surface.
8. The method for manufacturing a rare earth magnet joint according to any one of claims 1 to 7, further comprising the steps of: applying a primer to the adjacent surface of the rare earth magnet on which the coating is to be formed and / or to at least a part of the coating already formed on the adjacent surface, and then forming the coating.
9. In a rare earth magnet joint formed by joining a plurality of rare earth magnets, for at least one pair of rare earth magnets constituting the rare earth magnet joint, a cured coating of a resin composition is applied by an inkjet method to at least a part of adjacent surfaces of the two rare earth magnets adjacent to each other across an edge of a joining surface where one surface of the rare earth magnets are in contact with each other and joined, and the coating has a film density of 1.15 to 1.21 g / cm 3 wherein rare earth magnets are joined together by the coating.
10. 10. The rare earth magnet joint according to claim 9, wherein the coating has a pencil hardness of 6H or more according to JIS K5600.